2001
DOI: 10.1523/jneurosci.21-15-05535.2001
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Expressed KCNQ Potassium Currents and Native Neuronal M-Type Potassium Currents by the Anti-Convulsant Drug Retigabine

Abstract: acid ethyl ester] is a novel anticonvulsant compound that is now in clinical phase II development. It has previously been shown to enhance currents generated by KCNQ2/3 K ϩ channels when expressed in Chinese hamster ovary (CHO) cells (Main et al., 2000;Wickenden et al., 2000). In the present study, we have compared the actions of retigabine on KCNQ2/3 currents with those on currents generated by other members of the KCNQ family (homomeric KCNQ1, KCNQ2, KCNQ3, and KCNQ4 channels) expressed in CHO cells and on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

53
400
4
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 379 publications
(460 citation statements)
references
References 38 publications
53
400
4
1
Order By: Relevance
“…Retigabine, an antiepileptic drug that was recently approved for clinical use, has been shown to activate native M-type currents (34), as well as KCNQ2, KCNQ3, KCNQ4, and KCNQ5 currents (25). A tryptophan residue in the S5 segment of KCNQ subunits is crucial for the effects of retigabine (25), although additional residues have also been implicated (16).…”
Section: Resultsmentioning
confidence: 99%
“…Retigabine, an antiepileptic drug that was recently approved for clinical use, has been shown to activate native M-type currents (34), as well as KCNQ2, KCNQ3, KCNQ4, and KCNQ5 currents (25). A tryptophan residue in the S5 segment of KCNQ subunits is crucial for the effects of retigabine (25), although additional residues have also been implicated (16).…”
Section: Resultsmentioning
confidence: 99%
“…Retigabine was subsequently shown to activate all four KCNQ isoforms expressed in the brain (KCNQ2-5), but not the isoform responsible for the cardiac M-current (KCNQ1). 151 Study of chimeras derived from KCNQ1-KCNQ2 152 or KCNQ1-KCNQ3 151 showed that S5, S6, and the pore loop contribute to retigabine sensitivity. Point mutations further indicated that a tryptophan residue on the cytoplasmic end of S5 is essential for the action of retigabine.…”
Section: Voltage-gated Potassium Channelsmentioning
confidence: 99%
“…In heterologous expression systems, it primarily targets KCNQ3-containing channels and, to a lesser extent, KCNQ2 homomers (9). Bath application of retigabine to hippocampal CA1 pyramidal cells from wild-type mice led to the rapid development of an outward current reflecting the opening of KCNQ channels ( Fig.…”
Section: Role Of Kcnq3 In the Imahp In Hippocampusmentioning
confidence: 99%